Density Functional Theory Adsorption of Atoms on Cytosine - Ahmad Zabidi, Noriza; Ahmad Rosli, Nazrul; Abu Kassim, Hasan; Shrivastava, Keshav N. (Malaysian Journal of Science, 2010)
The density functional theory is used to optimize the geometry of a cytosine molecule and those of several atoms including H2 molecule, placed in the centre of the hexagon of the cytosine molecule. The adsorption of all of the first group atoms H, Li, Na, K, Cs and Fr, the second group atoms, Be, Mg, Ca, Sr, Ba , the halogens, F, Cl, Br, I and At and the rare gas atoms, He, Ne, Ar, Kr, Xe and Rn has been calculated. All these atoms are optimized and the adsorption energy has been found. The adsorption energy is found to be maximum for Ba, which is a second group element and minimum for hydrogen. In every group, as the atomic number increases, the corresponding adsorption energy increases. Apparently, in several cases, large adsorption energies are found.